Mercado de carbono e projetos REDD+ como ferramentas de combate às mudanças climáticas - Galindo, Igor Torres (Universidade Federal de São Carlos, 2025)
The increase of emissions of greenhouse gases caused by anthropogenic actions intensified the global warming phenomenon, causing so-called climate changes and extreme weather events. The effects can already be noticed on the Earth’s surface and the urgency for solutions brings with it the search for strategies and tools that aim to mitigate the effects of climate change through reduction of emissions. In this context, the carbon market and its mechanisms, as REDD+, emerges. The strategy of reducing emissions from deforestation and degradation appears as an feasible alternative in respect of forest conservation. A case study of a real project was analyzed with the aim of understanding its true impacts in practice and verifying its relevance as a preservation agent, demonstrating the objectives to be achieved that benefit the environment and society. The results show the practical efficiency with regards to reducing greenhouse gas emissions and fighting climate change and also reinforce the importance of searching for alternatives that increasingly aim to reduce emissions and the mitigation of anthropogenic impacts caused on the environment, seeking to converge towards a future in which there is a sustainable relationship between man and nature.
Carbon market and REDD+ projects as tools for climate changes mitigation
Keywords: Mercado de carbono; GEE; GHG; REDD; Carbon Market; ENGENHARIAS; 13. Ação contra a Mudança Global do Clima